Estudo comportamental e eletrofisiológico de crianças e adultos com dislexia do desenvolvimento em uma tarefa de decisão lexical - Oliveira, Darlene Godoy de (2014)
Developmental Dyslexia has a main deficit the effective word recognition, which is a complex cognitive processing due perceptual skills, language and later stages of syntactic and semantic integration. Among the wide range neurobiological evidence related this disorder in childhood and across life-span, event-related potential measures indicates differentiated pattern in amplitudes, latencies and hemispheric processing in different stages of sensory/perceptual, orthographic, phonologic and semantic processing. These electrophysiological evidences are related to behavioral deficits and to reading compensatory mechanisms in Dyslexia. The present thesis aimed to verify and compare the behavioral and electrophysiological pattern of adults (Study 1) and children and adolescents (Study 2) with and without Dyslexia during a Lexical Decision task. The sample of Study 1 comprised by 20 dyslexics and 23 normal readers with college degree. In Study 2, twenty dyslexic children and adolescents and twenty normal readers were included. All participants were matched for gender, age and educational level and performed a battery of intelligence, reading, writing and phonological awareness tasks. The lexical decision task was composed by regular high frequency words in Brazilian Portuguese, quasi-words derived from real words and pseudowords not derived from real words. Behavioral results in both studies revealed that dyslexics had worse accuracy and increased reaction times in all lexical categories. ERPs analysis of Study 1 indicated greater amplitudes in right P100 for both groups. The N170, N400 and LPC were reduces on the left hemisphere for dyslexics. N400 and LPC were higher for words and quasi-words, stimuli that are represented on orthographic and phonological lexicon. Correlations data in all sample verified reduced N170 and LPC left amplitudes associated with good performance in behavioral reading, writing and phonological awareness tests. GD with slow behavioral performance exhibited higher N170 and N400 on left hemisphere. Study 2 results indicated greater P100 on right hemisphere for all lexical categories in all sample, and reduced for DG. N170 were higher at left side and for quasi-words. N400 were higher for words and quasi-words, as well reduced in left hemisphere for DG. LPC were higher in left hemisphere for pseudowords and reduced in dyslexics. Correlational results revealed reduced left N170, N400 and LPC in dyslexics with slow behavioral performance. Controls with slow performance exibithed higher P100 amplitudes, as well higher left N400 if they had higher reading skills. Generally, ERP analysis indicated lacks of hemispheric specialization in dyslexics. The absence of ERP group differences on Study 2 can be related to developmental reading fluency processes, although we verified positive correlations between higher linguistic ERP amplitudes and better behavioral performances for both children and adults. We conclude that dyslexic children and adults present differenciated ERP amplitudes and hemispheric distribution during reading in Brazilian Portuguese.